Positive and negative perceptions of Bumiputra and non-Bumiputra students on professional qualification - Abd Rashid, Noor Asidah; Abdul Hamid, Fatima (2017)
Bumiputra and non-Bumiputra students may come from various economic backgrounds and culture. This may influence their perception on their career choice of pursuing a professional accounting qualification.Thus, this study investigates the difference in positive and negative perceptions of Bumiputra and non-Bumiputra students on pursuing a professional qualification upon graduation.A questionnaire survey method was used to collect the data from final year accounting students from five public and three private universities in Malaysia.Means and independent sample t-tests results were analysed.Results indicated that there are only a few significant differences between Bumiputra and nonBumiputra students on positive and negative perceptions on becoming professional accountants.As perception frames action, these findings would be useful to the Malaysian Institute of Accountants as well as professional bodies to attract both Bumiputra and non-Bumiputra graduates to become professional accountants.